Nurses facing health misinformation: How to spot scientific articles misuse? - Beatriz Jiménez-Gómez; Regina Moldes Moro; María del Carmen Águila Pollo; Paula García Montesinos; Sergio Segado-Fernández; Iván Herrera-Peco (Archives of Nursing Research, 2022)
Currently, large amounts of health information, mainly in the social media field, have led to an infodemic which, together with the vast misleading and inaccurate information that can be accessed, represents a substantial public health issue. Healthcare professionals can help to identify and even prevent the dissemination of such information, as well as to lead the struggle against it by denying it. Therefore, the aim of this paper is to propose a guide to be used for the detection of health misinformation focused on health professionals. The model is based on an in-depth analysis, focused on assessing the contextualization of the type of scientific document, the possibility of extrapolation of the information, the causality, as well as the quality of the scientific evidence given. Besides requesting an effort from healthcare professionals to prevent the spread of health disinformation, we believe it is essential to offer tools to easily detect it, whereby training in research methodology is the main tool for healthcare professionals in the fight against misinformation and its negative implications on people's health